UBASH3B Is a Novel Prognostic Biomarker and Correlated With Immune Infiltrates in Prostate Cancer - Wang, Zijun; Wang, Yinhuai; Peng, Mou; Yi, Lu (Frontiers in Oncology, 2020)
Background: UBASH3B (STS1) is an important gene that negatively regulates T-cell receptor signaling in activated T-lymphocytes and involved in cancers. However, the function of UBASH3B in cancer and the correlation between UBASH3B and tumor-infiltrating immune cells are still unclear. Methods: PCR and immunohistochemistry have been applied to measure mRNA and protein expression of UBASH3B in prostate cancer. Clinical features were recorded and Kaplan-Meier curves were plotted. Based on the TCGA-PRAD database, patients were divided into low UBASH3B expression group and high UBASH3B expression group to construct lncRNA-miRNA-mRNA network and analyze GO and KEGG pathways. Single gene analysis method was performed using GSEA to interpret gene expression data in prostate cancer. The PPI network was constructed using STRING and the correlation between UBASH3B and tumor-infiltrating immune cells was analyzed by TIMER and CIBERSORT. Results: Our results show that the mRNA and protein expression levels of UBASH3B are up-regulated in prostate cancer. The abundant expression of UBASH3B in PCa is associated with poor prognosis. The subnetwork of UBASH3B contains three lncRNAs (MIAT, LINC01297, MYLK-AS1) and four miRNAs (hsa-miR-200a-3p, hsa-miR-455-5p, hsa-miR-192-5p, hsa-miR- 215-5P). UBASH3B expression changes involves 28 KEGG pathways and 18 hallmark gene sets are significantly enriched in high UBASH3B expression, and 1 gene set is significantly enriched in low UBASH3B expression. The protein-protein interaction network shows the interaction between UBASH3B and LCP2, which is an immune related gene. TIMER shows that UBASH3B infiltrates in 8 types of immune cells and is involved in tumor-infiltrating naive B cells, resting memory CD4+ T cells, activated memory CD4+ T cells, follicular helper T cells, regulatory T cells, resting dendritic cells, activated dendritic cells, M2 macrophages, resting mast cells, resting NK cells and activated NK cells. Conclusions: In conclusion, UBASH3B may be a novel potential prognostic biomarker and associated with tumor-infiltrating immune cells in prostate cancer.